How Well are We Teaching Students Programming? Perceptions of Students of Their Programming Experience - Mow, I Chan (GSTF International journal on computing, 2015)
This paper describes a study aimed at investigating student's perceptions on their computer programming experiences at the National University of Samoa (NUS). The objectives were to: gauge student opinions on interest and experience, level of mental engagement, motivation, with respect to their programming skills and experience; identify perceived areas/topics of difficulty in the programming curriculum; and identify perceived deficiencies in learning support and the learning environment. Students in the 3 Java programming classes at the NUS were given questionnaires to complete. The results in this paper are limited to responses from one class, HCS286. The preliminary findings focusing on the first objective is the subject of an earlier paper and focuses on findings on gauging student opinions on interest, experience, level of mental engagement and motivation with respect to their programming skills and experience. Findings from the current study provide useful feedback which can be used in improving the student learning environment for such a cognitively challenging subject.